“Be a Liberation Whatever”: Social Justice Literacy in a Living-Learning Community - Faith Kurtyka (Journal of the Assembly for Expanded Perspectives on Learning, 2019)
This article describes an assessment of a living-learning community— part residence life, part community service, and part academics—to understand how students learn “social justice literacy.”